Slaframine toxicosis in Brazilian horses causing excessive salivation - Borges, Alexandre Secorun [UNESP]; Oliveira-Filho, J. P. [UNESP]; Simon, J. J.; Palumbo, M. I. P. [UNESP]; Imerman, P. M. (Wiley-Blackwell, 2012)
Ingestion of food contaminated with slaframine, an alkaloid produced by Rhizoctonia leguminicola, causes a mycotoxicosis, characterised by excessive salivation. Twenty-eight horses demonstrated this clinical sign after the consumption of alfalfa hay which on inspection showed dark patches on many of the stems. The presence of slaframine (1.5 ppm) in this hay was confirmed by gas chromatography and mass spectroscopy. This is the first equine slaframine toxicosis case reported in Brazil.
Keywords: horse; mycotoxicosis; Rhizoctonia leguminicola; slaframine; salivation